Genetic diversity of aromatic rice in Bangladesh (Research in Agriculture Livestock and Fisheries, 2017)
The nature and magnitude of diversity in 53 aromatic rice genotypes was evaluated in rain fed condition at BRAC Agricultural Research and Development Centre, Gazipur in 2012. The Euclidian method of divergence analysis indicated the presence of appreciable amount of genetic diversity in the material. These aromatic rice genotypes were grouped into six clusters where cluster I was the largest. Inter-cluster distances were larger than the intra-cluster distance revealed that there situated considerable genetic diversity among the genotypes. Based on positive value of vector I and II days to 50% flowering, seed length, and grain yield per hill had maximum contribution towards genetic divergence. Maximum yield contributing traits were accumulated in cluster V and as a result higher grain yield (42.0 g/hill) was obtained in this cluster. The genotypes of cluster V can be used in hybridization program to produce higher yielding breeding materials with all other clusters. The genotypes Cluster IV and cluster V were found most suitable for the respective characters and can be used as potential donor for future breeding programs.Res. Agric., Livest. Fish.4(1): 1-6, April 2017